Construções retóricas do discurso publicitário de condomínios residenciais - Alves, Maria Cristina Dias (2009)
The real estate advertisement presents some peculiarities owing to the products advertised, i.e., high value goods that cannot be consumed by the time of the purchase (do not exist in concrete). What is advertised is to become simulated in a hyper-realistic image of product and in a prototype of decorated apartment by the consumption experience at the sales stand. The real estate compares to a mass consumption product in relation to its serial assembly line, which alienate the worker from the final process. Advertising, as a myth of our time, occupies an intermediate ranking between production and consumption by classifying products, wherein the residential real estate obtains a sense: it acquires a name, a brand, a “conceptual packaging”, all of which distinguish it. On the occasion of the launch, the real estate has even not been edified, however, it “already exists” in the magic universe of advertisement, which starts in the advertisement and extends to the sales stand. In our work we have carried out two analysis movements on residential real estate launching advertisements in the city of São Paulo: The Discourse Analysis to verify the production conditions and the senses it comprises and the Rhetoric Analysis to verify the employed persuasive elements, which are focused on the reason or emotion. In this manner have we investigated the construction of the products personality and their advertisements, which catch the imaginary and seduce with identity models and life style.